THE "BUSINESS EXCELLENCE" MECHANISM FOR ASSESSING WOMEN’S ENTREPRENEURIAL ABILITIES AND ITS METHODOLOGICAL FOUNDATIONS. - Gulchehra, Narzullayeva (Центр Научных Публикаций (buxdu.uz), 2024)
The article presents analytical information about the mechanisms of formation and development of women’s entrepreneurial abilities, methods of "business excellence" assessment of women’s entrepreneurial abilities and their methodological foundations